2009
DOI: 10.1073/pnas.0903207106
|View full text |Cite
|
Sign up to set email alerts
|

Human origins: Out of Africa

Abstract: Our species, Homo sapiens, is highly autapomorphic (uniquely derived) among hominids in the structure of its skull and postcranial skeleton. It is also sharply distinguished from other organisms by its unique symbolic mode of cognition. The fossil and archaeological records combine to show fairly clearly that our physical and cognitive attributes both first appeared in Africa, but at different times. Essentially modern bony conformation was established in that continent by the 200 -150 Ka range (a dating in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 41 publications
(46 reference statements)
1
52
0
1
Order By: Relevance
“…But based on brain size, ecology, and toolkits, it seems clear that the earliest hominins (e.g., australopithecines) did not have modern language, although they might have had some DCL precursors. Although things become less clear within the genus Homo, most experts accept that Neanderthals lacked at least some component of modern language (see Paleontological data section and Mellars, 1989;Tattersall, 2009). It is also clear that by the time modern humans dispersed out of Africa (by 60 thousand years ago), we had the full package of modern language DCLs, since all humans around the world have the same essential capacity to acquire any language.…”
Section: Conceptions Of Protolanguagementioning
confidence: 99%
“…But based on brain size, ecology, and toolkits, it seems clear that the earliest hominins (e.g., australopithecines) did not have modern language, although they might have had some DCL precursors. Although things become less clear within the genus Homo, most experts accept that Neanderthals lacked at least some component of modern language (see Paleontological data section and Mellars, 1989;Tattersall, 2009). It is also clear that by the time modern humans dispersed out of Africa (by 60 thousand years ago), we had the full package of modern language DCLs, since all humans around the world have the same essential capacity to acquire any language.…”
Section: Conceptions Of Protolanguagementioning
confidence: 99%
“…Considering the role of the parietal areas in the perception and management of the relationships between inner and outer world (Bruner, 2010a), a two-part model of the evolution of modern humans might also explain some of the differences between early (Middle Stone Age/Middle Paleolithic) and late (Later Stone Age/ Upper Paleolithic) modern human cultures (Klein, 2000(Klein, , 2008Foley and Lahr, 2003;Wynn and Coolidge, 2003;Coolidge and Wynn, 2005). It has been long suggested that morphological and behavioral modernity could have been decoupled along the evolution of H. sapiens and that 'modernity' evolved not as a single package but as a combination of characters evolved in different times and places (Stringer, 2006(Stringer, , 2007Tattersall, 2009). If physical and cognitive attributes have evolved separately in modern humans, it is not surprising to find geographically isolated populations, such as Jebel Irhoud, that display a subset of modern cranial traits while retaining non-modern brain morphology.…”
Section: Phylogeny and Evolutionmentioning
confidence: 99%
“…It is now widely accepted that the species Homo sapiens, to which all modern humans belong, evolved in Africa before leaving to populate the rest of world (Tattersall, 2009). In order to successfully populate new and challenging environments hominins must have developed versatile and robust behaviors and survival strategies, with the most apparent hominin adaptation for versatility being the adoption of extra-genetic learning strategies such as social learning (Tomasello, 1999).…”
Section: Introductionmentioning
confidence: 99%